2019
DOI: 10.9734/ajrb/2019/v5i130083
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Histological Changes Associated with Azo Food Dye (Tartrazine) in Male Albino Rats

Abstract: Aim:To study the effect of chronic exposure of tartarzine at ADI doses on some biochemical parameters of male albino rats. Study Design: The design involved chronic study. In the study, the experiment was divided into phase 1, 2, and 3 which lasted for 30, 60 and 90 days respectively. In each phase, 40 rats were used and were divided into treatment and control groups. The treated groups were given 7.5 mg/kg of tartrazine orally on daily basis over the stipulated periods while the control groups were not treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 15 publications
7
16
0
Order By: Relevance
“…However, significant increase was seen in ALT after 60 days of treatment. The result of ALT is in line with the report of [6,39]. Amin et al [6] reported increase in ALT concentration in rats administered with 15 mg/kg and 500 mg/kg bodyweight.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, significant increase was seen in ALT after 60 days of treatment. The result of ALT is in line with the report of [6,39]. Amin et al [6] reported increase in ALT concentration in rats administered with 15 mg/kg and 500 mg/kg bodyweight.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, when liver enzymes were considered, GGT and ALP indicated no significant difference after 30 and 60 days of treatment which is also in agreement with the reports of [39]. Elekima et al [39] documented non-significant increases in ALP in rats treated with tartrazine at ADI dose over a period of 60 days. However, Mehedi et al [38] reported significant increase in ALT and GGT after 13 weeks of tartrazine administration at a dose of 0.1% in female rats but such increase was not reported in male rats.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…They reported no significant change in the absolute and relative weight of the ovary when rats were treated with tartrazine at a dose of 0.1%, 0.45%, 1% and 2.5% for a period of 13 weeks. More so, our finding agrees with the report of Elekima et al [1]. They also observed no significant change in the absolute weight of the ovary when rats were given tartrazine at a dose of ADI doses over a period of 30 and 60 days.…”
Section: B Treated Rats 30 Days: Normal Oocyte (O) With Zona Pellucsupporting
confidence: 93%
“…Colour in the form of powder, pastes or semi fluid is added in a wide variety of food items like beverages, baking flavors, candies and other food items to improve appearance, attractiveness and taste [1,2]. These colors are able to influence or stimulate appetite, giving the consumer a quality perception [3].…”
Section: Introductionmentioning
confidence: 99%